Enhancement of biohydrogen production from palm oil mill effluent (POME): A review. (12th December 2022) - Mahmod, Safa Senan; Arisht, Shalini Narayanan; Jahim, Jamaliah Md; Takriff, Mohd Sobri; Tan, Jian Ping; Luthfi, Abdullah Amru Indera; Abdul, Peer Mohamed
Abstract: Palm oil mill effluent (POME), a wastewater from the most significant agricultural industry in Southeast Asia is produced in tremendous amounts that requires proper management to mitigate its negative environmental effects. The feasibility of treating POME in a closed dark fermentation (DF) system to replace the existing inefficient open ponding treatment has been thoroughly investigated. Theoretically, the maximum H2 yield obtained by DF process is 4 molH2 /molglucose, however, it is not achievable due to the nature of POME. In this study, several enhancement methods for increasing H2 yield and DF process stability were discussed. An apprehension into the different pre-treatment methods on POME including physicochemical, chemical and biological and their effects on the characteristics of POME including pH, temperature, sugar content, solid content, viscosity, nutrients and by-product toxicity on the biohydrogen production and effluent quality were reviewed. Various bioreactor designs were used for biohydrogen from POME, the modifications applied on the system design to increase the stability and productivity of POME treatment have been examined. Moreover, higher biohydrogen productivity could be obtained with the addition of nanoparticle nutrients and introducing genetically modified H2 -producing bacteria. Finally, further investigation in the future shall focus on the development of a more inclusive and efficient POME treatment via DF process that favours biohydrogen production, environmental benign and economically viable. Graphical abstract: Image 1 Highlights: Enhancement of H2 production from POME in DF was reviewed. Enhancement efficiency was based on increase in H2 yield and pollutant removal. Dilute acid pretreatment has a promising effect on the performance of DF. Simple modification in bioreactor design could greatly improve process performance. Genetic engineering and nanoparticle technology on H2 were discussed.